The Role of Transformational Leadership in Managing Human Resources for Organizational Innovation Case Study in A State Electricity Company - Amir; Adiwijaya; Firly Juanita Surahman; Syam, Mukhlisah (Future Science, 2024)
Transformational leaders provide autonomy and responsibility to employees, allowing them to take initiative and contribute actively to organizational goals. The aim of this research is to understand the role of transformational leadership in influencing human resource management strategies to support innovation within the State Electricity Company. The research method used in this study is Systematic Literature Review (SLR). The results of this study indicate that transformational leadership is not just about managing organizations but also about building a culture that continuously seeks ways to improve and innovate, ensuring that the State Electricity Company remains competitive and relevant in facing the challenges of the future electricity industry.